2014
DOI: 10.1089/bfm.2014.0043
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Inflammatory Cytokine Profile of Human Breastmilk

Abstract: A longer lifetime duration of breastfeeding may decrease the risk of breast cancer by reducing breast inflammation and mitigating inflammatory cytokine expression during postlactational involution. However, little is known about how the inflammatory cytokine profile in human breastmilk changes over time. To study temporal trends in breastmilk cytokine expression, we measured 80 human cytokines in the whey fraction of breastmilk samples from 15 mothers at 1, 4, 8, and 12 weeks postpartum. We used mixed models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
(39 reference statements)
1
20
1
1
Order By: Relevance
“…Consistent with other studies, we found that many cytokines are present in detectable levels in human milk and in higher concentrations in colostrum (Agarwal et al, 2011; Castellote et al, 2011; Chollet-Hinton et al, 2014; Hawkes et al, 2000; Trend et al, 2016). Chemokines associated with innate immunity (MCP-1, MIP-1β, IP-10, IL-8, RANTES) and cytokines that impact epithelial cell function (TGF-βs) or induce lymphocyte maturation (IL-6 and IL-7) were almost universally detectable.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies, we found that many cytokines are present in detectable levels in human milk and in higher concentrations in colostrum (Agarwal et al, 2011; Castellote et al, 2011; Chollet-Hinton et al, 2014; Hawkes et al, 2000; Trend et al, 2016). Chemokines associated with innate immunity (MCP-1, MIP-1β, IP-10, IL-8, RANTES) and cytokines that impact epithelial cell function (TGF-βs) or induce lymphocyte maturation (IL-6 and IL-7) were almost universally detectable.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas cytokine expression decreases during the first month of lactation in transitional breast milk, immune components appear relatively stable in mature breast milk [21].…”
Section: Discussionmentioning
confidence: 98%
“…Colostrum is the first milk produced by the mammary when the tight junctions in the mammary epithelium are open (1). It is rich in cytokines (anti-inflammatory cytokines, pro-inflammatory cytokines) and other immune agents such as secretory Immunoglobulin A (sIgA) and lactoferrin (2)(3)(4)(5)(6)(7). These immune agents can provide bacteriostatic, bactericidal, antiviral, anti-inflammatory and immunomodulatory protection against infection (8).…”
Section: Introductionmentioning
confidence: 99%